Exploring the dynamics of cash waqf: a critical analysis of its implementation in Malaysia - Awang Abd. Rahman @ Jusoh, Amilah; Awang, Abdul Bari (IIUM Press, International Islamic University Malaysia, 2018)
This paper explores the dynamics of the waqf institution in Islam, with special focus on cash waqf and its implementation in Malaysia. Its combined flexibility and accuracy is important to the real purpose of the waqf in its implementation. Its dynamics are first explored through its meaning and objectives as well as special features of waqf and cash waqf with special focus on the status of the endowed asset (mawqūf). The second part focuses on the critical evaluation of the current cash waqf practices in Malaysia. It is found that the special attention on the endowed asset ought to be maintained in order to preserve its original purpose. Waqf offers all kinds of assistance and is not confined to crisis management. Possessing the highest liquidity rate, cash waqf constitutes an important financial mechanism, especially given the current state of economic affairs. Its nature must be maintained, as suggested by those jurists who allow cash to be considered as an endowed asset (mawqūf) and also those who do not favour it, in order to maintain the perpetuity of the benefit. Only by adhering to this special arrangement, the real spirit of waqf and its dynamics can be preserved and further developed in order to fulfil the economic needs of society.